Effect of Earnings Quality on the Firm Value of Consumer Goods Manufacturing Companies in Nigeria - Fajuyagbe, Bamikole Samson (Journal of Danubian Studies and Research, 2023)
This study examines the effect of earnings quality on the firm value of Nigerian firms that manufacture consumer products using static and dynamic models. Earnings quality was proxied by an accrual-based score, and firm value was proxied by the ratio of share price to book value. From 2012 to 2021, data from the annual reports of a selection of consumer goods manufacturers listed on the Nigerian Group of Exchanges was used as a secondary source of information. In this investigation, panel data regression and panel vector autoregressive are used as estimation methods. According to the static model, earnings quality has a positive but insignificant impact on the value of a company. In addition, the results of the granger causality test demonstrated that earnings quality cannot be used to predict future firm value, and that earnings quality has a negative and insignificant influence on firm value in the short term. Thus, it was determined that earnings quality has no effect on the long-term or short-term firm value. The study concluded that earnings quality has no significant impact on the firm value of Nigerian companies that manufacture consumer products. In light of this, the study recommends that the management of companies that manufacture consumer products use an accrual-based score as a measure of earnings quality for informative earnings management, which will increase firm value.